Philosophy of Material Logics Learning Tauhid the Nature of Two-Twenty Work Habib Usman bin Yahya in Islamic Religion Education - Nurhadi Nurhadi (ISLAMIKA, 2019)
Aqidah Tauhid is belief and knowledge which addresses the form of God, the obligatory nature, the nature of jaiz and the impossible nature. Islam among complete religions teaches Tawheed ahlisunnah waljama'ah, in the frame of ‘Asy’ariyah Maturidiyah, which contains the characteristics of twenty charities ma'rifah, because awaluddin ma'rifatullah" started the religion of knowing God ". Knowing God means having a religion, not knowing Allah means having no religion (infidel). Five Pillars of Islam, the first pillar of the science of monotheism or aqeedah. Learning tauhid must understand the three laws, namely law ‘Aqal, adat and syariat. These three laws are called theories of philosophical aqeedah, the easiest theory to know God with the twofold concept. It consists of four parts, namely the nature of nafsiyah (wujud), salbiyah (qidam, baqa, mukhalafatu lil hawadist, qiyamu bi nafsihi and wahdaniyat), maknawi (qudrat, iradat, knowledge, hayat, sama ', basar and qalam) and maknawiyah (presence , student, aliman, hayyan, sami'an, basiran and mutakalliman). These twenty traits have ta'aluq, namely the nature of qudrat and iradat ta'aluq ta’sir, the same nature ', basar and the knowledge of ta'aluq incisive, the nature of kalam ta'aluq is done. The twenty characteristics are grouped into two properties, namely istighna 'and iftiqar. This is the core content of the content "laa ilaaha illa allah". The second monotheism is the monotheism of the Prophet Muhammad who has the mandatory four characteristics, namely: siddiq, trust, tabigh and fatanah.